Frequency and recognisability of the main tourist attractions and locations in Maribor - Horvat, Uroš; Stubičar, Nina (Journal for Geography, 2021)
Frequency and recognisability of the main tourist attractions and locations in Maribor In the first part of the article, with the help of the analysis of printed travel guide books and web blogs, the frequency of occurrence of the main tourist attractions and locations in Maribor in selected media is shown. As many as 70 different attractions, institutions or areas in Maribor appear in 13 printed travel guide books, which have tourist use or are interesting for visitors and tourists. The authors note that travel guides focus mainly on the area of the city centre (Lent, Glavni trg and Grajski trg), while outside it, only the areas of Piramida and Pohorje are most often mentioned. Among the individual attractions, the House of the Old Vine, the Plague Column and the Cathedral Church are the most frequently mentioned. The analysis of 12 web blogs showed an even greater focus on the most important tourist attractions in the city centre, as they mention only 37 attractions, institutions or locations in Maribor. In the second part of the research, the authors present the results of a survey of tourists in 2021, namely the extent to which they recognize and visit individual tourist attractions in the city. They were divided into main (especially in the city centre) and alternative tourist attractions and locations, with which the authors wanted to check out the interest of tourists for less visited attractions. The results of the survey confirmed the major interest of tourists only in the main tourist attractions and locations in the city centre, and outside it only in the area at the foot of Pohorje mountain, while interest in alternative tourist locations was very low. The results are a reflection of the fact that a tourist visit to Maribor still largely depends on transit tourists, who mostly visit Maribor for only a day or two. Unfortunately, the results contradict the efforts of tourist experts in Maribor, who promote and invite tourists to extend their visit to Maribor, especially with the presentation of many experiences in Maribor and its surroundings, especially intended for lovers of wine and cuisine, nature research and sports activities.